Comparison of Stone Matrix Asphalt mixtures with polymer-modified bitumen and shredded waste plastics. Issue 4 (1st October 2016) - Sarang, Goutham; Lekha, B.M.; Krishna, G.; Ravi Shankar, A.U.
Abstract : Stone Matrix Asphalt (SMA) is a gap-graded bituminous mixture characterised with its improved rut resistance and durability. It has comparatively higher proportion of coarse aggregates and binder mastic with bituminous binder and mineral filler. Drain down of mastic content at various stages of construction is a common issue with SMA, and generally, some fibre additives are used to stabilise the mixture or a modified bitumen is used as the binder material. In this study, shredded waste plastics (SWP) are used instead of other stabilising additives, to prepare SMA mixtures with conventional viscosity graded (VG) 30 bitumen. Mixtures were prepared with four different levels of SWP content, and another mixture without any stabilisers was also prepared using polymer-modified bitumen (PMB). Specimens were prepared in superpave gyratory compactor (SGC) for all mixtures at different bitumen contents to determine volumetric and Marshall properties, and optimum bitumen content (OBC) was calculated for each mixture. Tensile strength, moisture susceptibility, rutting resistance and fatigue behaviour were also determined for all mixtures at corresponding OBC. From the available results, the optimum level of SWP in SMA mixture was determined as 8% by weight of bitumen. The study showed that even though mixture with PMB performed the best, SMA with 8% SWP provided comparable results. Based on the present investigation, waste plastic in suitable dosage can be recommended in SMA, instead of a stabilising additive.